A RASCH MODEL ANALYSIS: VALIDITY OF THE COLLEGE STUDENT’S EMOTIONAL INTELLIGENCE INSTRUMENT - Tessa Tessa; Dodi Suryana (Universitas Pendidikan Indonesia, 2023)
Emotional intelligence is an essential aspect because it can influence individual success or success. Therefore, a valid and reliable emotional intelligence instrument is needed. This research was conducted to analyze the validity and reliability of the emotional intelligence instrument for students. This research was conducted using a quantitative approach and a cross-sectional study design with random sample selection and analysis using the RASCH Model. The RASCH model analysis has the advantage of creating evenly spaced measurement scales to provide accurate information about participants and the quality of the items producedThe results of the analysis show that items from the Emotional Intelligence instrument are well received by college students with Cronbach alphas values that include special categories. This is because it represents the interaction between the respondent and the instrument item. Person reliability score results are included in a special category as a measure of the consistency of responses of respondents. Item Reliability score are included in a special category as an indicator of the quality of the item items in the instrument.